(untitled) (Italian Journal of Public Health, 2012)
Human medicine and animal medicine have developed as "one medicine" starting from the times in which their bases were laid until the mid 18th century when specialisation proved necessary.The separation has been the logical consequence of the construction of different fields of action, made necessary by the evolution of the disciplines and of the social and economic context, but common areas have remained relevant and are strongly required by modern developments...